Pengaruh Fasilitas Kerja Dan Kompensasi Finansial Melalui Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Amanah Insanillahia Kabupaten Tanah Datar - Dani, Putri Rama; Arita, Sri (Universitas Negeri Padang, 2024)
The purpose of this study is to determine the impact of work facilities and financial compensation on employee performance at PT Amanah Insanillahia Tanah Datar District. A questionnaire was used to collect data. This study's population consisted of all 171 employees of PT Amanah Insanillahia, with a sample size of 64 people. In this study, Simple Random Sampling was used as the sampling technique. Partial Least Squares (PLS) analysis was used with the assistance of SmartPLS 4.0 applicants. According to the study's findings, (1) work facilities have a significant impact on the performance of employees at PT Amanah Insanillahia, Tanah Datar Regency. (2) Financial compensation has no discernible effect on the performance of PT Amanah Insanillahia, Tanah Datar Regency employees. (3) Workplace facilities have a significant impact on PT employees' work motivation. Tanah Datar Amanah Insanillahia Regency (4) Financial compensation influences the work motivation of PT Amanah Insanillahia Tanah Datar Regency employees. (5) Work motivation has a significant impact on the performance of PT Amanah Insanillahia Tanah Datar Regency employees. (6) Workplace facilities have a significant impact on employee performance PT Amanah Insanillahia Tanah Datar Regency (7) Financial compensation via work motivation has a significant impact on the performance of PT Amanah Insanillahia Tanah Datar Regency employees.